2013
DOI: 10.1515/bnm-2013-0012
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial efficacy, cytotoxicity, and ion release of mixed metal (Ag, Cu, Zn, Mg) nanoparticle polymer composite implant material

Abstract: Medical devices made of polymers are often protected against infection-relevant biofilm formation by embedding nanoparticles as a source of bioactive metal ion release. Safe application of such nanocomposites requires finding the optimal ion dose and identifying the cross-effects caused by material mixtures. This study investigated the safety and antimicrobial efficacy of thermoplastic polyurethane (TPU), which is widely used for medical devices, e.g., catheters containing zinc, silver, copper and magnesium na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 48 publications
1
31
0
Order By: Relevance
“…When the productivities obtained for this pilot-scale nanoparticle synthesis are transferred to composite materials, the potential of this method becomes visible. Doping a polymer with 1 wt % of metal nanoparticles, as done by Sowa-Söhle et al [56], with the amount of nanoparticles synthesized after 1 h of laser ablation can lead to composite yields of up to 410 g. In case lower concentrations like 0.1 wt % are doped, composite yields within the kilogram range can readily be obtained (Fig. 4 a).…”
Section: Composite Synthesismentioning
confidence: 98%
See 3 more Smart Citations
“…When the productivities obtained for this pilot-scale nanoparticle synthesis are transferred to composite materials, the potential of this method becomes visible. Doping a polymer with 1 wt % of metal nanoparticles, as done by Sowa-Söhle et al [56], with the amount of nanoparticles synthesized after 1 h of laser ablation can lead to composite yields of up to 410 g. In case lower concentrations like 0.1 wt % are doped, composite yields within the kilogram range can readily be obtained (Fig. 4 a).…”
Section: Composite Synthesismentioning
confidence: 98%
“…However, the biocompatibility of both the matrix and the nanoparticle is crucial [51,72] and the safety of the product has to be ensured. In general, the polymer matrix needs to be nontoxic, and the nanoparticles have to be immobilized within the matrix [56,72]. The immobilization is necessary since direct contact of nanoparticles with biological tissues and cells, i.e., when using functionalized wound dressings or implants, can be toxic [51] or the nanoparticles can enter the body through a wound [72].…”
Section: Biomedicinementioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, silver nanoparticles embedded in polymer matrices show less cytotoxicity than bared ones. Sowa-Söhle et al [76] found that thermoplastic polyurethane-silver nanoparticle composites with nanosilver concentrations from 0.01 to 1.0 wt % were non-cytotoxic to mouse fibroblass cells but toxic to bacteria. Oliveira et al [77] reported the preparation of PVA-Ag hydrogel samples with 0.25 and 0.50 wt % silver precursor.…”
Section: Inhibition Of Bacterial Growth By Pva/go-agnps Nanocompositesmentioning
confidence: 99%